2001
DOI: 10.1080/00207540110068790
|View full text |Cite
|
Sign up to set email alerts
|

A review of agile manufacturing systems

Abstract: About a decade ago, the agile manufacturing paradigm was formulated in response to the constantly changing`new economy' and as a basis for returning to global competitiveness. While agility means di erent things to di erent enterprises under di erent contexts, the following elements capture its essential concept: agility is characterized by cooperativeness and synergism (possibly resulting in virtual corporations), by a strategic vision that enables thriving in face of continuous and unpredictable change, by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(135 citation statements)
references
References 48 publications
0
124
0
4
Order By: Relevance
“…At the end of this article, in appendix I, we present the final Network of Concepts corresponding to both dyads exposed herein in according to how they understood the topic been reinforced (Agile Manufacturing); for dyad 6 see Figure 8, and for dyad 2 see Figure 9). For each graphical representation, we can observe that each one is very different, but they share fundamental concepts like those cited in (Sanchez & Nagi, 2001) with respect to Agile Manufacturing, example of these concepts are adaptability, human factors, competitivity, cooperation, customers, e-commerce, technology, and information systems. Particularly in the case of dyad 2 (Figure 9), the shape of the network attracts our attention because we found that it could be influenced by a similar scheme from the reading of the article of Gunasekaran (Gunasekaran, 1998), therefore we dismiss the idea that the shape of the network were totally new in contrast to others.…”
Section: Methods For Analyzing the Processmentioning
confidence: 99%
“…At the end of this article, in appendix I, we present the final Network of Concepts corresponding to both dyads exposed herein in according to how they understood the topic been reinforced (Agile Manufacturing); for dyad 6 see Figure 8, and for dyad 2 see Figure 9). For each graphical representation, we can observe that each one is very different, but they share fundamental concepts like those cited in (Sanchez & Nagi, 2001) with respect to Agile Manufacturing, example of these concepts are adaptability, human factors, competitivity, cooperation, customers, e-commerce, technology, and information systems. Particularly in the case of dyad 2 (Figure 9), the shape of the network attracts our attention because we found that it could be influenced by a similar scheme from the reading of the article of Gunasekaran (Gunasekaran, 1998), therefore we dismiss the idea that the shape of the network were totally new in contrast to others.…”
Section: Methods For Analyzing the Processmentioning
confidence: 99%
“…Increasingly, traditional centralized and sequential manufacturing process planning, scheduling, and control mechanisms are being found insufficiently flexible to respond to changing production styles and high-mix lowvolume production environments (Shen, 1999). The traditional approaches limit the expandability and reconfigurability of the manufacturing systems (Sanchez, 2001). The centralized hierarchical organization may also result in much of the system being shut down by a single point of failure, as well as plan fragility and increased response overheads (Yang, 2003).…”
Section: In the Concept Of Intelligent Manufacturing Systemsmentioning
confidence: 99%
“…Agile organizational culture is reflected in market focus with internal systems facilitating employee's empowerment and participation (Holbeche, 2011). Agility is characterized by an information infrastructure connecting the constituent parties and partners within a united network (Sanchez & Nagi, 2001), and this connectivity might improve the coherence between members. Coherence, strong relations and trust between managers and employees are required for participative decision making (Ho et al, 2013).…”
Section: Participative Decision Making (Pdm)mentioning
confidence: 99%
“…These practices include enhancing internal and external cooperation such as establishing partnerships with suppliers, and considered the first choice of operational strategy for an agile firm (Goldman et al, 1995). Internal and external cooperation leads to synergy and plays an important role in developing OA (Sanchez & Nagi, 2001). The agile firm should gain the strategy of opportunistic pool with other firms, even with competitors, in order to respond to market demands (Yaghoubi et al, 2011).…”
Section: Cooperative Practices (Cp)mentioning
confidence: 99%